PENGARUH LITERASI KEUANGAN DAN MITIGASI RISIKO TERHADAP KEBERLANGSUNGAN UMKM DI KOTA JAMBI - Muhammad Irham; Agustina Mutia; Fauzan Ramli (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
MSMEs have a large contribution to regional income and state income, play a role in reducing the unemployment rate because of their labor-intensive nature, this business can absorb a lot of workers. Micro, Small and Medium Enterprises (MSMEs) can improve the standard of living of many people. The research aims to determine and analyze the influence of financial literacy and risk mitigation on the sustainability of MSMEs. Using quantitative methods of data analysis, Determinant Coefficient Test. The sample taken was 96 respondents who were MSMEs in Jambi City. Financial Literacy and Risk Mitigation together have a significant effect on sustainability. It is proven that the adjusted R square value (coefficient of determination) is 0.443 or 44%. Shows that the influence of Financial Literacy and Risk Mitigation on the Sustainability of MSMEs has an influence of 44% and the remaining 56% is influenced by other variables outside this research.